Changes in prosocial behaviors among children with behavioral problems following incredible years parenting program - Masiran, Ruziana; Ibrahim, Normala; Awang, Hamidin; Poh, Ying Lim (Frontiers Media, 2022)
Parenting programs often train parents in improving their parenting practices and parent-child relationship to reduce behavioral problems in children. However, the children’s prosocial behaviors are less examined as an intervention outcome in these programs. This study aimed to evaluate the effectiveness of the Incredible Years parenting program (IYPP) for Malaysian parents of school-going children and its sustainability in improving the children’s prosocial behaviors. This randomized controlled study involved pre- and post-intervention assessments at 2 and 14 weeks. Mothers of children aged 6-12 years (n = 70) recruited through the pediatrics and the child and adolescent psychiatric clinics were randomly assigned to the parenting program or a waitlist control condition. The mothers rated their children’s prosocial behaviors using a self-administered questionnaire. The program ran two to three hours weekly for 14 weeks. Several modifications were made to the program to accommodate public health control during the pandemic. Children in the intervention group showed a notable but non-significant increase in prosocial skills. However, subsequent score decline at follow-up may suggest a lack of evidence that the program is potentially effective in improving prosocial behaviors among school children who are at risk of or already having behavioral problems.